جمالية توظيف التراث في مسرحية بابا مرزوق ليحيى موسى - سمية, سالمي; قويدر, قيطون (جامعة الوادي - University of Eloued, 2023)
ملخص: يتناول هذا البحث مسألة توظيف التراث في النص المسرحي الجزائري، ذلك أنّ التراث هو نتاج الثقافة المدونة والمنقولة والشفهية لمجتمع ما، أو مجتمعات مختلفة، ولأنّه يحمل طابعا خاصا فإنّ استلهامه لابد أن يؤدي إلى إثراء أي عمل عربي على مستوى النصوص المسرحية، فتنوعت مصادر هذا التراث بينما هو محلي وبينما هو إنساني. وسأبحث في الموضوع بالتأصيل لهذا الأمر والوقوف عند آليات ذلك، والنظر في الدلالة الجمالية التي أضافها توظيف التراث للنص المسرحي على مستوى الشكل والمضمون، ومن بين كتاب المسرح في الجزائر الذين اشتغلوا على هذا الأمر نجد الكاتب المسرحي يحيى موسى في مسرحيته بابا مرزوق الأسطورة الإنسانية العالمية بطابعها المحلي، وهي التي وقع اختياري عليها لمعالجة هذه المسألة. Abstract: This research mainly treats the question of employing heritage in the Algerian theatrical text as heritage is the product of the written, transmitted and oral culture of any given society, or other different societies. Due to its special character, its inspiration must lead to enriching any Arab work at the level of theatrical texts. Thus, the sources of this heritage are varied between what is local and what is human. Accordingly, my research will be focusing on investigating this issue and its mechanisms together with studying the aesthetic. semantics added by the heritage’s employment of the theatrical text at the level of form and content. For my research, I chose the Algerian playwright, Yahya Moussa, with his play ‘Baba Marzouk’ which presents the global human legend.
مقال
Keywords: الجمالية، التراث، المسرح، التوظيف; aesthetics, heritage, theater, employment